Semi-periphery and capital-intensive advanced technologies: the construction of Argentina as a nuclear proliferation country - Hurtado de Mendoza, Diego Fabian (2015)
Throughout the second half of the twentieth century a varied collection of pressure mechanisms were deployed from nuclear technology exporting countries — mainly from the US — to obstruct the development of a group of semi-peripheral countries’ autonomous nuclear capabilities. Argentina was part of this group. This article focuses on how “fear” of nuclear proliferation was used by US foreign policy as one of the most effective political artifacts to construct and protect an oligopolistic nuclear market. Spread by the press and by some prestigious social science sectors from the US and some European countries, a persistent and dense discourse production was devoted over several decades to the bizarre practice of “calculating” the alleged hidden intentions of those semi-peripheral countries which aspired to dominate as many technologies of the nuclear fuel cycle as possible.